2015
DOI: 10.1093/abbs/gmu135
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of resveratrol through the suppression of NF-κB and JAK/STAT signaling pathways

Abstract: Resveratrol, the most important ingredient extracted from Polygonum cuspidatum, exerts cytoprotective effects via anti-inflammatory actions in vitro. In this study, we investigated this effect of resveratrol on the lipopolysaccharide (LPS)-induced inflammatory response and its underlying molecular mechanism of action in RAW264.7 murine macrophages. Results showed that resveratrol down-regulated the expression of inducible nitric oxide synthase (iNOS) and interleukin-6 (IL-6), therefore, suppressed the producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(85 citation statements)
references
References 32 publications
2
83
0
Order By: Relevance
“…Therefore, STAT1 could contribute to iNOS upregulation in the diabetic lung [96,97]. The pro-inflammatory role of the JAK/STAT pathway is well established in the macrophage [98,99,100]. Antioxidants such as resveratrol have been reported to inhibit inflammatory pathways in mouse macrophages by inhibiting JAK/STAT signaling pathways, suggesting that DM-induced oxidative stress in the lung, contributing to DM-induced lung inflammation, could be mediated via JAK/STAT activation [98].…”
Section: Putative Signaling Mediating Diabetes-induced Microvasculmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, STAT1 could contribute to iNOS upregulation in the diabetic lung [96,97]. The pro-inflammatory role of the JAK/STAT pathway is well established in the macrophage [98,99,100]. Antioxidants such as resveratrol have been reported to inhibit inflammatory pathways in mouse macrophages by inhibiting JAK/STAT signaling pathways, suggesting that DM-induced oxidative stress in the lung, contributing to DM-induced lung inflammation, could be mediated via JAK/STAT activation [98].…”
Section: Putative Signaling Mediating Diabetes-induced Microvasculmentioning
confidence: 99%
“…The pro-inflammatory role of the JAK/STAT pathway is well established in the macrophage [98,99,100]. Antioxidants such as resveratrol have been reported to inhibit inflammatory pathways in mouse macrophages by inhibiting JAK/STAT signaling pathways, suggesting that DM-induced oxidative stress in the lung, contributing to DM-induced lung inflammation, could be mediated via JAK/STAT activation [98]. A recent study reported that Sitagliptin, a dipeptidyl peptidase-4 inhibitor, improved diabetic cardiomyopathy and cardiac fibrosis induced by streptozotocin in rats through inhibition of JAK2 and STAT3 phosphorylation [101].…”
Section: Putative Signaling Mediating Diabetes-induced Microvasculmentioning
confidence: 99%
“…In murine RAW 264.7 macrophages and microglial BV-2 cells, resveratrol also inhibited microglial activation by suppressing the NF-κB pathway [54]. In another study, resveratrol showed anti-inflammatory effect by suppressing the NF-κB pathway in RAW 264.7 murine macrophages in a dose-dependent manner [55]. These studies suggest that resveratrol has anti-inflammatory, antioxidant, anti-carcinogenic effects and can strengthen hemodynamic structure, which in turn can positively affect the aging process and longevity.…”
Section: Gene Expression and Regulation In Mammalian Cells -Transcripmentioning
confidence: 93%
“…Resveratrol also inhibited HMGB1 release in other systems possibly via suppressing the JAK/STAT1 signaling pathway [150,151], which is important in mediating HMGB1 hyperacetylation and translocation [152]. Sirtuin-1 was recently identified as a novel mediator of deacetylation of HMGB1 [153].…”
Section: Active Compounds From Chinese Herbal Medicine For Targeting mentioning
confidence: 99%